Differential effects of GLI2 and GLI3 in regulating cervical cancer malignancy in vitro and in vivo. (November 2018) - Zhu, Haiyan; Xia, Lu; Shen, Qi; Zhao, Menghuang; Gu, Xiang; Bouamar, Hakim; Wang, Bingzhi; Sun, Lu-Zhe; Zhu, Xueqiong
Abstract Advanced, recurrent, or persistent cervical cancer is often incurable. Therefore, in-depth insights into the molecular mechanisms are needed for the development of novel therapeutic targets and the improvement of current therapeutic strategies. In this study, we investigated the role of GLI2 and GLI3 in the regulation of the malignant properties of cervical cancer. We showed that down-regulation of GLI2, but not GLI3, with an inducible GLI2 shRNA inhibited the growth and migration of cervical cancer cell lines, which could be rescued by ectopic expression of GLI2. GLI2 appeared to support cell growth by regulating the mitosis, but not the apoptosis, of the cervical cancer cells. Mechanistically, these functions of GLI2 were in part mediated by the activation of AKT pathway. Knockdown of GLI2, but not GLI3, also inhibited xenograft growth of cervical cancer cells in vivo. Finally, analysis of TCGA data showed that high levels of GLI2, but not GLI3, conferred a poor prognosis in cervical cancer patients. These observations for the first time suggest that GLI2, but not GLI3, exerts a tumor-promoting role in cervical cancer and may be targeted as a novel therapeutic strategy. GLI transcription factors, which mediate the Hedgehog pathway, are over-expressed in cervical cancer. RNA interference reveals an essential role of GLI2, but not GLI3, in promoting proliferation and migration and xenograft tumor growth of human cervical cancer cells. Mechanistically, the function of GLI2 is mediated by protein kinase B (AKT), and may be targeted as a novel therapeutic strategy.